The problem of deficiency of factors of the anticoagulant system. Clinical case - O. B. Gordeeva; A. V. Dobrotok; I. V. Andreeva; E. V. Dovgan; O. A. Egorova; V. S. Kargin (Лечащий Врач)
Background. In available foreign publications, there is evidence of a high incidence of mortality in the development of septic conditions in children in case of deficiency of factors in the natural anticoagulant system. It is known that deficiency of factors in the anticoagulant system can be congenital and acquired. Congenital deficiency is quite rare, and acquired deficiency can be observed against the background of inflammatory reactions in chronic, infectious diseases, oncopathology. Of particular concern is the lack of proper attention to patients of children's age category, the clinical picture of thrombosis in which may be erased. At the same time, it is in children that timely diagnosis and prevention, as well as identifying the presence of a risk of such events, can play a key role in preventing disability. Severe complications of physiological anticoagulant deficiency are thrombotic events and skin necrosis. The presented clinical case describes an episode of acquired protein S deficiency in a child.Objective. To analyse a diagnostically complex clinical case from real medical practice in order to draw attention to the problem of acquired physiological anticoagulant deficiency against the background of bacterial complications after viral infection in children.Materials and methods. The article describes a clinical case of acquired deficiency of the anti-clotting system factor complicated by the development of DIC, skin necrosis and venous thrombosis of the lower limbs after a viral infection in a young child. The peculiarity of this case is the debut of the disease with skin lesions of the extremities against the background of the development of disorders in the platelet and plasma links of haemostasis with a developing deficiency of components of the plasma link of haemostasis. To establish the diagnosis, the patient underwent an in-depth study of the haemostasis system to clarify the deficiency of factors of the natural anticoagulant system (protein C, protein S, antithrombin III).Conclusion. This clinical observation shows the importance of careful history taking and the necessity of timely examination of the patient when bacterial complications develop after a viral infection. The clinical case also demonstrates the importance of multidisciplinary approach and continuity between doctors of different specialities in the diagnosis of severe disorders of coagulation and anti-coagulation systems, which contributes to adequate assessment of the detected disorders, prediction of the risk of possible complications (haemorrhagic and thrombotic syndromes), and preservation of patients' quality of life.